Spirituality for Mission - Sueiro, Samuel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
One of the characteristics of the pastoral ministry of Pope Francis is the insistence on assuming with a new impulse the Christian responsibility of proclaiming the Gospel. In this sense, his magisterium is situated in perfect continuity with the perspectives opened up by the Second Vatican Council for the Church in the contemporary world. Much of the theological thinking of recent decades has shown the intrinsic correlation between ecclesial mission and spirituality. Based on the Council’s texts and on the contributions of some outstanding theologians of the conciliar generation, this reflection seeks to highlight the theological foundations of a renewed missionary impulse in the Church from the correlation between spirituality and mission, especially in the light of the evangelical counsels of poverty, chastity and obedience, as dynamisms of the theological life.